Speech Act Strategies in Social Media Interactions Pragmatic Analysis of TikTok Comments: Adrianus Gude, I Made Juliarta (Focus Journal : Language Review, 2026)
This study aims to analyze speech act strategies in social media interactions, particularly in TikTok's comment section, using a pragmatic approach. TikTok, as a short video-based platform, functions not only as an entertainment medium but also as a discursive space where users perform various social actions through language. This study uses a descriptive qualitative method with data in the form of user comments on TikTok posts that have a high level of interaction. Data collection was carried out through non-participant observation and documentation, while data analysis included reduction, classification, pragmatic interpretation, and drawing conclusions. The theoretical framework used includes Austin and Searle's speech act theory, Grice's cooperative principle, Brown and Levinson's politeness theory, and Fairclough's critical discourse perspective. The results show that expressive speech acts and indirect directives are the most dominant strategies, manifested through implicature, humor, and politeness strategies. These strategies are used to convey criticism, build solidarity, negotiate identity, and reproduce and challenge power relations in political discourse, education, entertainment, and da'wah. These findings confirm that speech acts in TikTok comments are not neutral, but rather function as ideological and contextual social practices in digital culture, particularly among Generation Z.